Case report: Identification of novel fibrillin-2 variants impacting disulfide bond and causing congenital contractural arachnodactyly - Li, An-Lei; He, Ji-Qiang; Zeng, Lei; Hu, Yi-Qiao; Wang, Min; Long, Jie-Yi; Chang, Si-Hua; Jin, Jie-Yuan; Xiang, Rong (Frontiers in Genetics, 2023)
Background: Congenital contractural arachnodactyly (CCA) is an autosomal dominant connective tissue disorder with clinical features of arthrogryposis, arachnodactyly, crumpled ears, scoliosis, and muscular hypoplasia. The heterozygous pathogenic variants in FBN2 have been shown to cause CCA. Fibrillin-2 is related to the elasticity of the tissue and has been demonstrated to play an important role in the constitution of extracellular microfibrils in elastic fibers, providing strength and flexibility to the connective tissue that sustains the body’s joints and organs. Methods: We recruited two Chinese families with arachnodactyly and bilateral arthrogryposis of the fingers. Whole-exome sequencing (WES) and co-segregation analysis were employed to identify their genetic etiologies. Three-dimensional protein models were used to analyze the pathogenic mechanism of the identified variants. Results: We have reported two CCA families and identified two novel missense variants in FBN2 (NM_001999.3: c.4093T>C, p.C1365R and c.2384G>T, p.C795F). The structural models of the mutant FBN2 protein in rats exhibited that both the variants could break disulfide bonds. Conclusion: We detected two FBN2 variants in two families with CCA. Our description expands the genetic profile of CCA and emphasizes the pathogenicity of disulfide bond disruption in FBN2.